Un documento inedito sul soggiorno di Leonardo da Vinci alla corte di Francesco I - Sammer, Jan (Achademia Leonardi Vinci, 2021)
According to a payment recorded in the Second Account Book of Jean Sapin at the Archives nationales de France, a royal painter at Amboise named Laurent Boudry appointed Giovanni Francesco Melzi as the executor of his testament and Leonardo da Vinci as his heir. Although nothing further is known about the deceased painter, Boudry’s bequest testifies to the close ties with the local artistic community that Leonardo and Melzi had established in their new domicile.